Determinants of Trade Partner Concentration: An Analysis for European Countries - António Afonso; José Alves; Lucas Menescal; Sofia Monteiro (CESifo GmbH, 2024)
After computing the Gini and Herfindahl-Hirschman indexes for exports and imports partner concentration for a set of 31 European countries between 1995 and 2023, we analyse the role of macroeconomic, institutional and uncertainty effects on the partner concentration (diversification) of exports and imports. From our analysis, we disentangle different effects, namely that while global GDP leads to an increase in concentration in both exports and imports, internal rates of return increase exports diversification, reducing it for imports. Additionally, European uncertainty reduces the concentration of the product countries' origin/destination for imports and exports, respectively. Our results provide a comprehensive set of results that enable public authorities and firms to minimize their risks when trading with the exterior.
Keywords: C33; E02; F14; F32; F41; G15; 330; exports; imports; Gini index; Herfindahl-Hirschman index; determinants of concentration